A semantic similarity measure in the context of semantic queries. (6th January 2009) - Blazquez-del-Toro, Jose M.; Fisteus, Jesus Arias; Centeno, Vicente Luque; Sanchez-Fernandez, Luis
In the current age of information, applications must deal with the heterogeneity of data. Many efforts in the state of the art try to solve this issue in an automatic fashion and the emergence of semantic Web technologies has boosted these techniques. However, the usage of these technologies gives place to new problems that must be sorted out. One of these problems comes from the utilisation of ontologies, where concepts arranged in a hierarchy are used. In many applications, this requires measures of semantic similarity between these concepts. In this paper, we introduce an innovative solution to tackle this problem.